Effectiveness of bubble continuous positive airway pressure as a primary mode of respiratory support in preterm neonates with respiratory distress syndrome at district level tertiary care hospital (Indian Journal of Child Health, 2020)
Background: Continuous positive airway pressure (CPAP) has become a useful modality in the management of respiratory distress in preterm babies. CPAP when applied to preterm infants with respiratory distress syndrome (RDS) is associated with benefits in terms of reduced respiratory failure and reduced mortality. Objectives: The objectives of the study were to evaluate the efficacy of bubble CPAP in preterm neonates with RDS requiring respiratory support and to study the risk factors associated with its failure. Materials and Methods: A prospective observational study was done on 243 preterm neonates (gestational age [GA] 28 to ?37 weeks) with a diagnosis of RDS admitted from January 2016 to November 2017. All the eligible preterm neonates were started on bubble CPAP with binasal prongs. Surfactant was administered when indicated. Results: A total of 243 preterm neonates were enrolled in this study with a mean GA of 32.40 weeks and birth weight of 1831.49 g. One hundred and fifty-one (62.1%) were male and 92 (37.9%) were female. The mean age of starting of CPAP was 13.44 h of life and antenatal steroid coverage was 3.2% only. Of the 243 neonates, 195 neonates were successfully weaned off CPAP. Among the 48 neonates who failed CPAP, 27 neonates were ventilated, of which 20 (74.1%) survived. The predictors of CPAP failure were GA <32 weeks, birth weight <1.5 kg, and delayed initiation of CPAP. Conclusion: The efficacy of CPAP in neonates with mild-to-moderate RDS in preterm neonates is very well demonstrated despite the low usage of antenatal steroids, surfactant, and delayed initiation of CPAP. Extreme preterm, very low birth weight neonates with severe RDS on chest X-ray are at risk of failure of CPAP.